2019
DOI: 10.1177/1120672119841216
|View full text |Cite
|
Sign up to set email alerts
|

Binocular treatment in adult amblyopia is based on parvocellular or magnocellular pathway

Abstract: Introduction: Amblyopia is speculated to be an untreatable disease in the patient, who is beyond the critical period of vision; however, currently, it is treatable in adults. Purpose: This study aimed to elucidate whether the treatment is useful in both anisometropic amblyopia and strabismic amblyopia. In addition, the differences were detected between anisometropic amblyopia and strabismic amblyopia after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…In the treatment of amblyopia, the appropriate application of drugs to improve microcirculation and vasodilator may contribute to the improvement of visual acuity, which needs further research and exploration. In adulthood, treatment of amblyopia has long been widely known to be impossible; however, it has been recently shown that amblyopia can be treated with the aid of some special binocular perceptual learning programs, such as “Diploma Gabor Orientation Coherence Training” ( 17 ). For adult patients with amblyopia, it is worthy of clinical study whether giving appropriate drugs to dilate blood vessels and improve microcirculation will still improve vision.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of amblyopia, the appropriate application of drugs to improve microcirculation and vasodilator may contribute to the improvement of visual acuity, which needs further research and exploration. In adulthood, treatment of amblyopia has long been widely known to be impossible; however, it has been recently shown that amblyopia can be treated with the aid of some special binocular perceptual learning programs, such as “Diploma Gabor Orientation Coherence Training” ( 17 ). For adult patients with amblyopia, it is worthy of clinical study whether giving appropriate drugs to dilate blood vessels and improve microcirculation will still improve vision.…”
Section: Discussionmentioning
confidence: 99%
“…Dadurch können die Sehschärfe am amblyopen Auge, die Stereosehfähigkeit und die Erkennungsgeschwindigkeit verbessert werden [15]. Patienten mit Strabismus und Amblyopie profitieren auch von einem Sehtraining hinsichtlich Stereo-und Kontrastsehfähigkeit [16]. In der Presbyopietherapie konnte durch ein Wahrnehmungstraining mit niedrigen Kontrast-Gabor-Stimuli eine Verbesserung der Stereosehschärfe und visuellen Kognitionszeit erreicht werden [17].…”
Section: Hintergrund Und Fragestellungunclassified
“…8 Adults' visual systems have been found to demonstrate plasticity and may, therefore, benefit from treatment aiming to decrease suppression and to restore binocular functions. 9 This change in our perceptions has caused an increased interest in the binocular treatment of amblyopia, as amblyopes' monocularity is now regarded as functional and not as structural. Perceptual learning and dichoptic training are the principle focus of current research, with some early evidence of positive results.…”
Section: European Ophthalmic Reviewmentioning
confidence: 99%